PEMBERDAYAAN MASYARAKAT MELALUI PEMANFAATAN KORAN BEKAS MENJADI KERAJINAN TANGAN - Roy Wahyuningsih (BERNAS: Jurnal Pengabdian Kepada Masyarakat, 2022)
Paper is one of the most abundant wastes produced by humans, both by households and schools and offices. Paper recycled processing has many advantages including: increasing income, reducing environmental waste, saving energy, and helping the world from global warming. In general, an academic will produce a large amount of paper waste because all academic activities are directly related to paper. Academic paper waste can be obtained from activities in the office or activities carried out by students, and can be used as raw material for making paper recycling without having to pay a lot of money, but making it a value-added product.